Preparing Malaysia’s health care industry for IFRS sustainability standards - Long, Chiau Ming *; Woon, Chin Ong *; Ong, Hwai Chyuan * (Social Health Analytics Sdn Bhd, 2025)
Preparing for these new standards is not merely a compliance exercise; it is a strategic imperative for future-proofing key economic sectors and enhancing the integrity of the entire Malaysian capital market.